AN ANALYSIS OF SEMANTIC CHANGES IN JAKARTA POST - Luthfiyati, Dian; Khoirina, Najwa; Moh. Nurman; Almayda Dwi Shaputri, Zeppyca (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
This study is designed to produce and provide information that will help the researcher enhance their writing skills. Changing the shape of the meaning, as seen on the online news website